Programa virtual RCD para favorecer el dibujo en niños de 3 años de una institución educativa inicial, Trujillo, 2021 - Deza Peña, Alisson Gianella (2022)
This research emerged from the experiences gained in pre-professional internships at EI. N°1638 "Pasitos de Jesús" because it allowed me to show that children show little development with respect to children's drawing, so it was investigated to be able to help, as well as guide through distance education. Since it is very important that in early childhood education I achieved strengthening in children's drawing. The design of this research is basic descriptive propositional, with a sample consisting of 11 children of 3 years of age, to whom a test was applied to evaluate the level of development in children's drawing. Obtaining as a result that 50% were located at the starting level and only one child at the level achieved, justifying the elaboration of the proposal of a virtual RCD program, to strengthen the drawing in children of 3 years.